Digital Leadership for Agile Organization and Organizational Sustainability - Josua Panatap Soehaditama; Agustian Zen; Jumawan; Didin Sjarifudin; Tri Widyastuti; Bambang Karsono (East Asian Journal of Multidisciplinary Research, 2023)
This scientific article aims to provide a proof and justification and the final result is a contribution and adds treasures to existing research results, This scientific article uses a causative method with literature studies derived from scientific articles from reputable journals that have a good reputation. The results of this study then the qualitative variables in this study describe the findings in this scientific article related to digital leadership, agile organization and sustainability variables are proven, and strongly used, so that the researcher provides a perspective that in the scope of human resource management there are many variables from this scientific article, related to other variables that can be used in future research.